2016
DOI: 10.3390/ijgi5020012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Distribution of Urban Green Spaces and its Anisotropic Cooling Distance on Urban Heat Island Pattern in Baotou, China

Abstract: An essential part of urban natural systems, urban green spaces play a crucial role in mitigating the urban heat island effect (UHI). The UHI effect refers to the phenomenon where the temperature within a city is higher than that of the surrounding rural areas. The effects of the spatial composition and configuration of urban green spaces on urban land surface temperature (LST) have recently been documented. However, few studies have examined the effects of the directionality and distribution of green spaces on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 37 publications
(20 reference statements)
6
49
0
Order By: Relevance
“…Increasing the NDVI by 0.1 would lead to a decrease of surface temperature of 1.82 • C (2007), 0.51 • C (2011) and 1.82 • C (2015). Li et al reported a correlation between NDVI and the UHI effect in the city of Baotou, which has similar latitude to Harbin, during the growing season (July-August) [12]. We obtained a similar conclusion, namely that NDVI had a negative relationship with the UHI effect during summer.…”
Section: Relationship Between the Urban Heat Island And Green Spacesupporting
confidence: 82%
See 1 more Smart Citation
“…Increasing the NDVI by 0.1 would lead to a decrease of surface temperature of 1.82 • C (2007), 0.51 • C (2011) and 1.82 • C (2015). Li et al reported a correlation between NDVI and the UHI effect in the city of Baotou, which has similar latitude to Harbin, during the growing season (July-August) [12]. We obtained a similar conclusion, namely that NDVI had a negative relationship with the UHI effect during summer.…”
Section: Relationship Between the Urban Heat Island And Green Spacesupporting
confidence: 82%
“…Green space composition refers to the variety of land cover types (i.e., size, density and evenness of urban green space patches), and configuration is related to the spatial arrangement and layout (i.e., shape, aggregation and cohesion of patches) [8,9]. The size of urban green space has a strong influence on its cooling effect [10][11][12]. Green spaces of average-size (50 ha) can lower the temperature range 1.5-3.0 • C [13,14], while the larger ones (>150 ha) have a more substantial cooling effect on the surrounding temperature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Urban heat island intensity (UHII) is an important indicator to evaluate the severity of SUHI [65]. In this study, UHII is defined as the difference between the LST of each pixel and the mean surface temperature in HJ-1B images [66]. The approach tends to differ from the other regional or global UHII analyses that took "rural" area (a certain distance away from urban) as reference locations [67,68], since Shenzhen is the first city in China with no rural administrative system.…”
Section: Determination Of Urban Heat Islandmentioning
confidence: 99%
“…They provide key ecological functions such as carbon storage, soil conservation, noise buffering, maintenance of air quality, reduction of air temperature etc. to protect and maintain bio diversity of the city (Bao et al, 2016). They contribute in a positive manner to maintain public health by facilitating appropriate space for physical exercise to improve physical and psychological well-being (Cohen et al, 2007;Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to that, a space of 0.41km 2 has to be kept as urban parks for 1000 residents (Nicholls, 2001). The Six Acre Standard of National Playing Fields Association of United Kingdom is another standard which recommends 0.24km 2 as the open space for 1000 residents (Nicholls, 2001).…”
Section: Introductionmentioning
confidence: 99%